Recognition of Symmetry as a Powerful Tool in Natural Product Synthesis - Cala, Lara; Gaviria, Mario A.; Kim, Scott L.; Vogel, Trenton R.; Schindler, Corinna S. (Synthesis, 2023)
The design of concise and efficient synthetic strategies to access naturally occurring, pharmaceutically active complex molecules is of utmost importance in current chemistry. It not only enables rapid access to these molecules and their analogues but also provides sufficient quantities for their biological evaluation. Identification of any symmetric or pseudosymmetric synthetic intermediates upon retrosynthetic bond disconnection of the target molecule holds the promise to significantly streamline the route towards the compound of interest. This review will highlight recent examples of successful natural product syntheses reported within the past five years that benefited from the recognition of symmetry elements during the retrosynthetic design.1 Introduction2 Examples2.1 Chondrosterin I and J2.2 (–)-Bilobalide A2.3 Delavatine A2.4 Oxycodone2.5 (–)-20-epi-vincamine and (–)-20-epi-eburnamonine2.6 Reserpine2.7 (–)-Berkeleyone A2.8 (–)-Maximiscin2.9 Aplysiasecosterol A2.10 (–)-Batrachotoxinin A2.11 (–)-Mitrephorone A3 Conclusions
Keywords: symmetry; natural products; retrosynthesis